2022
DOI: 10.1039/d2ta00966h
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of RuO6 octahedron distortion by enhanced A-site electronegativity in pyrochlore for acidic water oxidation

Abstract: Ruthenium-based pyrochlore oxides (A2Ru2O7) have emerged recently as state-of-the-art catalysts for acidic water oxidation, however, the stability still needs to be further improved. Exploring the relationship between the A-site cation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…10 At 10 mA cm −2 , Ho 2 Ru 2 O 7 catalyst shows an effective OER performance with an overpotential of 280 mV. 17 Meanwhile, the pyrochlore-type Y 1.7 Sr 0.3 Ru 2 O 7 18 and Nd 2 Ru 2 O 7 19 catalysts also show similar promotions. The pyrochlore oxides have a general formula of A 2 B 2 O 7 (here, A = alkaline or rare earth element; B = Ti, Ru, Sn, or Ir).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 At 10 mA cm −2 , Ho 2 Ru 2 O 7 catalyst shows an effective OER performance with an overpotential of 280 mV. 17 Meanwhile, the pyrochlore-type Y 1.7 Sr 0.3 Ru 2 O 7 18 and Nd 2 Ru 2 O 7 19 catalysts also show similar promotions. The pyrochlore oxides have a general formula of A 2 B 2 O 7 (here, A = alkaline or rare earth element; B = Ti, Ru, Sn, or Ir).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its robustness and long-term endurance, iridium (Ir) and its oxides are commonly used as commercial anode catalysts for PEM water electrolyzers. On the other hand, as Ir is an exceptionally rare element with a greatly increased price in recent years, ruthenium (Ru) is considerably less expensive than it . Meanwhile, some Ru-based oxides have shown better performance in the OER than Ir-based catalysts. , The low intrinsic activity of the reported Ru-based oxides, however, significantly reduced their catalytic efficiency. Therefore, developing novel effective Ru-based catalysts with lower noble metal concentrations and better intrinsic activity is still an open issue for acid–water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…2c and S6,† in the O 1s spectrum, the binding energies of adventitious oxygen (O adv ), oxygen vacancies (O V ), surface oxygen (O suf ) and lattice oxygen (O L ) are in descending order. 29 There is an overlap between the signal peaks of C 1s and Ru 3d (Fig. S7a†), and the valence state of Ru is further observed from the Ru 3p orbit.…”
Section: Resultsmentioning
confidence: 96%
“…The oxygen isotopes, 34 O 2 and 36 O 2 , released from the lattice oxygen-engaged OER were measured with 18 O labelled catalyst RuNiMoCrFeO x /CNT ( 34 O 2 comes from 18 O in the lattice with 16 O). 16,29,55 It is indicated that lattice oxygen is involved in the reaction and that the OER tends to proceed through the LOM. Further, in situ FTIR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation